Extremely rare cause of extrinsic compression of the stomach during esophagogastroduodenoscopy - Başara Akın, Işıl; Altay, Canan; Bengi, Göksel; Tarhan, Oktay; Seçil, Mustafa (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Başara Akın I, Altay C, Bengi G, Tarhan O, Seçil M. Extremely rare cause of extrinsic compression of the stomach during esophagogastroduodenoscopy. Turk J Gastroenterol 2019; 30(12): 1064-5.